Sports Civic Organizations-Conceptualization Issues and Trials - Szabados, György; Bácsné Bába, Éva; Fenyves, Veronika; Bács, Zoltán; Dajnoki, Krisztina (International Journal of Engineering and Management Sciences, 2018)
Lately published statistics of the Hungarian Central Statistical Office reveal such a phenomenon that in some years (between 2011 and 2015), that the number of sport related classic civic organizations has increased in the narrowing non-profit sphere. Inside, the role of sport has been intensified primarily among the sports associations, and not among the foundations. Considering the Central Statistical Office methodology, the questions arises and serves an issue that how can we conceptualize a sport civic organization. Regarding the same topic, we may face diverse databases, and it also seems that different conceptualization approaches exist, we do not have uniform regulation, and current data also raise further questions. Through a “from general to specific approach” we aim to reveal that in what way a civic organization can be considered to be a sports related civic organizations and also try to highlight the consequences of this plural approach.